Pengaruh Financial Attitude, Financial Knowledge dan Locus of Control Terhadap Financial Management Behavior Melalui Tingkat Pendidikan (Studi Pada Warung Kopi di Kecamatan Bungah) - Masjidah, Tutut Takhiyatul; Vilantika, Elok; Santoso, Rahmat Agus (Universitas Muhammadiyah Gresik, 2024)
Background - People have started to switch from traditional coffee shops to cafes as Gresik's business has grown. According to the data, the number of traditional coffee shops in Bungah District has been declining while the number of cafes has begun to increase. For their coffee shops to remain in business in the future, traditional owners must comprehend the significance of finances. Objective - This study aims to test the influence of financial attitude, financial knowledge and locus of control on financial management behavior through education levels in coffee shops in Bungah District. Design/Methodology/Approach - This study is quantitative in nature. Based on the Krejcie table, the study's population consisted of coffee shop owners in the Bungah District. A total of 181 coffee shops were sampled for the study using incidental sampling procedures, or sampling methods based only on chance. The findings of distributing questionnaires to respondents—coffee shop owners in the Bungah District—serve as the major data source for this study. Subjective data in the form of written questionnaire replies is the type of data that is employed. Multiple linear regression analysis is the type of analysis model that was employed in this investigation. Findings - The findings demonstrate that financial management behavior is influenced by the variables of financial attitude, financial knowledge, and locus of control. The relationship between financial attitude, financial knowledge, and locus of control on financial management behavior cannot be moderated by education level. Research implications - This study helps coffee shop owners maintain their financial behavior by educating them on the significance of financial attitudes, financial knowledge, locus of control, and educational attainment. Research limitations - Because this study was restricted to coffee shops in the Bungah District and employed a number of constrained variables, it was unable to accurately represent the financial practices of coffee shop owners generally.